Unannounced voices: curatorial practice and changing institutions - Badovinac, Zdenka 1958- (Sternberg Press, 2022)
"In our current era of global pandemic and violent political upheaval, the question must be asked: What is our future and whose voices will announce it? These can only be situated voices, each with its own body and space, formed through dialogue within their own communities and in reaction and resistance to dominant discourses. Museum director, curator, and writer Zdenka Badovinac argues that these situated voices of people, artworks, and exhibitions, rooted in the local, can bring incisive, productive change. The call of these voices, in rethinking art, curation, and institutions, is the subject of this powerful essay." -- Verlagsseite
Keywords: Prognose; Kunstausstellung